Routledge handbook of air power - Olsen, John Andreas 1968- (Routledge, 2018)
"The Routledge Handbook of Air Power offers a comprehensive overview of the political purposes and military importance of air power. Despite its increasing significance in international relations, statecraft and war, the phenomenon of air power remains controversial and little understood beyond its tactical-technological prominence. This volume provides a comprehensive survey designed to contribute to a deep and sophisticated understanding of air power. Containing contributions from academics and service personnel, the book comprises five sections: - Part I: Foundation: The Essence of Air Power - Part II: Roles and Functions: Delivering Air Power - Part III: Cross-Domain Integration: Applying Air Power - Part IV: Political-Social-Economic Environment: Air Power in its Strategic Context - Part V: Case Studies: Air Power in its National Context Examining a series of themes and factors that contribute to an understanding of the utility and applicability of air power, this Handbook focuses on the essence of air power, identifies its roles and functions, and places air power in its wider strategic and national contexts. The Routledge Handbook of Air Power will be of great interest to students of air power, strategic studies, defence studies, security studies and IR, as well as to military professionals and policymakers."--Provided by publisher
Keywords: Air power